HUBUNGAN KEMANDIRIAN DENGAN FAKTOR-FAKTOR PADA LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 2 CENGKARENG - Desnita Fitri; Crytianto Pranata; Anitha (Jurnal Nurse, 2020)
The aging process results in physical and mental changes, which affect the health and social conditions. This change affects the elderly independence in performing activities of daily living. Independence of the elderly is the behavior seen from the way the behavior of the elderly to ourselves and the environment associated with the ability to perform activities of health and social activities. The purpose of this study was to determine the factors associated with self-reliance of the elderly in Social Institutions â€œTresna Werdha Budi Mulia 2 Cengkarengâ€, West Jakarta. The design study is cross-sectional design (cross-sectional). Sample 81 respondents were collected by random sampling. Data is collected using questionnaire research instruments. Data analysis is kind of a frequency distribution and in the form of two different test proportions (chi-square) using statistic test. Of the 81 respondents the average yield of the elderly aged between 60-74 years is 75.3%, the highest elderly sex is 59.3% women, elderly people the most basic education 74.1%, elderly people who have good health as much as 55, 6%, elderly people who have good social relationships as much as 51.9%. As for a good level of independence as much as 71.6%. There was a significant relationship between the health condition of the independence of elderly (p value = 0.001).